2016
DOI: 10.21873/anticanres.11146
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Anticancer Agents of Diverse Natural Origin

Abstract: Recent progress is described in an ongoing collaborative multidisciplinary research project directed towards the purification, structural characterization, chemical modification, and biological evaluation of new potential natural product anticancer agents obtained from a diverse group of organisms, comprising tropical plants, aquatic and terrestrial cyanobacteria, and filamentous fungi. Information is provided on how these organisms are collected and processed. The types of bioassays are indicated in which ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
125
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(134 citation statements)
references
References 103 publications
1
125
0
4
Order By: Relevance
“…1,2 Of these, about 4700 are halogenated, 3 and just 5 contain a fluorine atom, 47 with no reports of natural fluorometabolites derived from fungi. Nature has been a fertile source for drug leads, particularly in the realms of anticancer and antimicrobial agents.…”
mentioning
confidence: 99%
“…1,2 Of these, about 4700 are halogenated, 3 and just 5 contain a fluorine atom, 47 with no reports of natural fluorometabolites derived from fungi. Nature has been a fertile source for drug leads, particularly in the realms of anticancer and antimicrobial agents.…”
mentioning
confidence: 99%
“…El-Elimat et al (2012) studied the chemical space of 105 compounds isolated from filamentous fungi using nine molecular descriptors, and compared them to other natural products and FDA-approved anticancer drugs. In that work it was concluded that fungal metabolites had a high overlap with the chemical space of anticancer drugs, which was an encouraging finding for the ongoing efforts to discover active anticancer compounds of fungal origin (Kinghorn et al, 2016). Gonzalez-Medina et al (2016) analyzed a larger data set with 207 fungal isolates, adding more information on structural complexity and diversity of the fungal metabolites.…”
Section: Introductionmentioning
confidence: 92%
“…Decisive advances in cellular and molecular biology have led to the improvement of chemotherapeutic management of cancer, but further efforts to discover new anticancer agents to overcome resistance and toxicity concerns, are still necessary. Because natural products are one of the major sources for lead compounds, exhibiting various modes of cytostatic action, in the last decades, interest has been focused on the use of natural products or their derivative with the aim of developing more efficacious chemotherapeutic agents …”
Section: Introductionmentioning
confidence: 99%